Strategi Meningkatkan Kinerja Pegawai Bagian Infomasi dan Pengolahan Data Sekolah Calon Perwira Angkatan Darat (Infolahta SECAPA AD) - Syarip Hidayat; Deddy Mulyadi; Nefi Aris Ambar Asmara (Jurnal Media Administrasi Terapan, 2023)
The purpose of this study was to find out and analyze how the strategy for improving the performance of the Staff of the Information and Data Processing Section of the Army Officer Candidate School was. This research method uses qualitative methods. The data analysis technique used is SWOT analysis. This research data collection using interviews, observation and documentation review. The results showed that the strategy that should be used to improve the performance of the Staff of the Information and Data Processing Section for Army Officer Candidates is Supporting Aggressive Strategies. The strategy that is feasible to be implemented for the Staff of the Information and Data Processing Section of the Army Officer Candidate School is the Institutional strategy by improving employee performance which focuses on efforts to develop human resources, namely improving the quality of adequate human resources through training activities, increasing collaboration with outside organizations and consultants. , Support the provision of adequate facilities and infrastructure, Increasing the use of structured education and training programs, Providing awards for loyal and professional employees, Increasing collaboration between employees, Involvement of Infolahta staff in determining organizational policies, Increasing budget for technology development and the latest innovations.